Water Gain: As a Common Good Becomes a Financial Opportunity - Fiorelli, Cristiana; Mele, Marco (International Journal of Economics and Financial Issues, 2017)
The purpose of this paper is to analyze how the water has become, indirectly, an important element also in the financial markets. Nevertheless, its particular nature, vital and instrumental for human life, gives this item a peculiarity: it is difficult to generate a price but, equally, it attracts the agents that operate in the financial markets. But, like any other commodity, the water is starting to take hold in the equity markets. There is, however, a difficulty. No one can change the water as it does for other financial instruments present in the stock markets. For this reason, the investors began to bet on companies that have as reference the water sector, considered a booming business. The present work aims to analyze the performance of the assets related to the water sector in the financial markets, comparing performance against major indexes, such as Dow Jones, Nasdaq and S&P 500. Next, we wanted to verify the existence of a causal link between the water and the SP500 index in order to confirm the hypothesis that the water has become, in financial markets, a safe haven. Keywords: Financial markets, US DJ Water, Granger test JEL Classifications: C32, F36, G15